A Midsummer Night Dream A Shakespeare Children's Story - Shakespeare, William (Sweet cherry Publisher USA, 2013)
A Midsummer Night$1 (Bs Dream is one of the most popular comedies of the legendary playwright, William Shakespeare. The playrevolves around Hermia and her best friend, Helena. Hermia runs away into the woods with her lover, Lysander, and Demetrius, the man of her father$1 (Bs choice, follows them. Helena follows Demetrius, as she is in love with him and wishes she could win his love. In the woods, they come across Oberon and Titania, King and Queen of the Fairies. Much confusion is created when Puck, one of the fairies, uses love drops on Lysander and Demetrius, which makes both of them fall in love with Helena.s
Shelving order "L"